#TITLE_ALTERNATIVE# - LESMANA (NIM: 29106338);Dosen Pembimbing: Amol Titus, MBA, ANDY
As countries in the world, including Indonesia, are moving towards “Less Cash” society, micropayment is often considered as the last piece of the so-called complete non-cash payment system. Over the past decades, earlier pieces of non-cash payment system have grown, developed, and evolved tremendously – to name a few: cheques, electronic fund transfers, ATM cards, debit cards, credit cards, and now is the time for micropayment, or more commonly known in the form of prepaid cards. Micropayment business/product in Indonesia started with the so called “closed loop” (single purpose single merchant) prepaid cards, such as department store gift cards, restaurants gift vouchers, mobile phone prepaid cards, and others. It is only since several years ago that the so called “open loop” (single purpose multiple merchants or multiple purposes multiple merchants) prepaid cards have started to be developed, pioneered by both the financial and non-financial sectors. Currently, there are nine institutions that have started to intensively develop and offer their micropayment products in Indonesia. Certainly more players, from both the financial and non-financial sectors, will emerge as the market grows and develops. This final project intends to focus on the growth and development of the micropayment products in Indonesia.